2022
DOI: 10.1097/ijg.0000000000001982
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Effectiveness of Eye Drop Self-instillation and Glaucoma Progression

Abstract: Among patients with glaucoma or ocular hypertension, ineffective self-instillation of eye drops was associated with an increased long-term risk of progression or advancement of treatment to incisional surgery. Purpose:The purpose of this study was to evaluate the association between the efficacy of self-instillation of eye drops and long-term glaucoma outcomes.Methods: In a previous study, video recordings of eye drop self-instillation by patients with glaucoma or ocular hypertension were graded as effective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, taken together with the findings of increased polypharmacy and utilization across multiple classes of intraocular hypotensive medications, this could reflect more severe or recalcitrant disease in these patients, necessitating more intensive medical therapy. Alternatively, patients with LHL may not use their medications optimally because of poor adherence and poor eye drop administration technique,4 leading to an increased risk of disease progression and more refills 10,11. It may also be that patients with LHL are overtreated, possibly because of the expectation that these patients may not consistently follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, taken together with the findings of increased polypharmacy and utilization across multiple classes of intraocular hypotensive medications, this could reflect more severe or recalcitrant disease in these patients, necessitating more intensive medical therapy. Alternatively, patients with LHL may not use their medications optimally because of poor adherence and poor eye drop administration technique,4 leading to an increased risk of disease progression and more refills 10,11. It may also be that patients with LHL are overtreated, possibly because of the expectation that these patients may not consistently follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, patients with LHL may not use their medications optimally because of poor adherence and poor eye drop administration technique, 4 leading to an increased risk of disease progression and more refills. 10,11 It may also be that patients with LHL are overtreated, possibly because of the expectation that these patients may not consistently follow-up. Previous research found Black and Hispanic persons are more likely to have LHL, compared with non-Hispanic White individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Patients cannot be relied upon to report dosing problems, as there is a significant mismatch between patients’ belief in their skills and their actual skills [63,65,66], and among those who experience difficulty with self-dosing 26% would not ask for help [67 ▪▪ ]. Poor instillation technique has been linked to an increased risk of progression in glaucoma patients [68 ▪▪ ].…”
Section: Common Causes Of Nonadherencementioning
confidence: 99%
“…However, the typically asymptomatic and chronic nature of the disease, complex dosing regimens, difficulty with instillation, lack of belief in the necessity of treatment, and chronic side effects associated with topical glaucoma medications undermine patient adherence and quality of life [ 1 5 ]. Although non-adherence to glaucoma therapy is known to contribute to the progression of glaucoma [ 6 8 ], nearly half of patients with glaucoma discontinue therapy within 6 months [ 9 ].…”
Section: Introductionmentioning
confidence: 99%